Diagnósticos e ações visando o controle de olhaduras gasosas não desejáveis em queijo - Carvalho, Gustavo Bacelar Moreira de (2018)
Late blowing is a serious defect in cheese production, it is associated with microorganisms and occurs during cheese ripening and has a major impact on the dairy industry. Mainly, this defect is caused by the clostridia growth. Late blowing is characterized by excessive gas production. Late blowing is a frequently observed defect in semi-cooked or cooked cheeses and prolonged maturation. Spore-forming bacteria of the genus Clostridium spp. have been identified as responsible for milk changes, especially the species Clostridium tyrobutyricum, C.butyricum and C. sporogenes. Another kind of gas producer microorganism in matured cheeses is propionic bacteria. Dairy propionic bacteria, mainly the specie Propionibacterium freudenreichii has an important role in the technology of gas hole cheese production, as Swiss cheeses, but when appearing this kind of gas hole in cheeses that do not have this characterist ic, it represents a defect of cheese, and this defect has been reported by a company headquartered in three different cities (Quintinos, Arapuã and Tiros) in the region of Carmo do Paranaíba in Minas Gerais. As we were presented, the occurring defect is when appearing gas hole in cheeses which they should not appear, indicating contamination of these cheeses by gas producing microorganisms. The study had as objective to promote corrective and preventive actions to control the occurrence of undesirable gas hole on cheeses. Microbiological analyzes (Colimetry, clostridia, propionic bacteria, and Staphylococcus and also total bacterial counts) and physical-chemical analyzes were carried out on samples of cheese, milk, water and whey. Some samples presented extremely high counts for some tests, and even if there is no current legislation for some of them, this represents a serious hygiene failure, reinforced by the fact that all bacteria identified can be originated in the digestive tract of humans and animals, such as: Hafnia alvei, Enterococcus faecalis, Staphylococcus saprophyticus and Klebsiella pneumonae. The possible causes of the contamination are: poor quality of raw milk, failure in pasteurization process, presence of biofilms in equipment and pipes by employees during handling, cheeses salting or combined causes.